2021
DOI: 10.1080/23802359.2021.1886885
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the complete chloroplast genome of the Solanum tuberosum L. cv. Favorita (Solanaceae)

Abstract: Potato ( Solanum tuberosum L.), a species of the family Solanaceae, is the fourth most important food crop worldwide. Solanum tuberosum L. cv. Favorita is a long oval, smooth, yellowish-skinned potato variety with green and plump leaves. It has a dry matter content of 17.7% and starch content of 12.4–14.01% in the tuber. In order to support more genetic data for the taxonomy of S. tuberosum , the complete chloroplast (cp) genome sequence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Employing next-generation sequencing (NGS) techniques, here, we sequenced for the first time the S. muricatum cp genome with accession number: OK326864, and compared to other cp genomes of seven Solanaceae species, which revealed similar genomic features. The S. muricatum cp genome is similar in gene content to most angiosperm species [26,[28][29][30]. The complete cp genome of S. muricatum was 155,681 pb in length, which was very similar to other Solanaceae genomes with a typical structure (two IR regions, LSC, and SSC).…”
Section: Discussionmentioning
confidence: 75%
“…Employing next-generation sequencing (NGS) techniques, here, we sequenced for the first time the S. muricatum cp genome with accession number: OK326864, and compared to other cp genomes of seven Solanaceae species, which revealed similar genomic features. The S. muricatum cp genome is similar in gene content to most angiosperm species [26,[28][29][30]. The complete cp genome of S. muricatum was 155,681 pb in length, which was very similar to other Solanaceae genomes with a typical structure (two IR regions, LSC, and SSC).…”
Section: Discussionmentioning
confidence: 75%
“…Solanum tuberosum L., commonly known as potato, is a versatile crop that produces tubers with immense nutritional and medicinal value . It is the fourth most cultivated food crop in China, surpassed only by rice, maize, and wheat . Potato virus Y (PVY) was first identified in potato farms of Europe in 1931 and has ever since been disseminated worldwide .…”
Section: Introductionmentioning
confidence: 99%
“…1 It is the fourth most cultivated food crop in China, surpassed only by rice, maize, and wheat. 2 Potato virus Y (PVY) was first identified in potato farms of Europe in 1931 and has ever since been disseminated worldwide. 3 In 1980, multiple successive reports highlighted the substantial damage to crop inflicted by PVY in major potato-growing regions of China, such as Heilongjiang and Henan.…”
Section: ■ Introductionmentioning
confidence: 99%
“…To obtain insight explore the position of S. erianthum within Solanaceae, phylogenetic analyses were performed using maximum likelihood (ML) in RAxML8.0 with 1000 bootstrap replicates (Stamatakis 2014 ) ( Figure 1 ) . Based on previous studies, the ML phylogenetic reconstructed based on whole chloroplast genomes from 62 Solanum plants and one sample Eucommia ulmoides as outgroup plants (Li et al 2021 ). ML analysis showed that S. erianthum was the most closely related species to S. violaceum with 100% bootstrap values.…”
mentioning
confidence: 99%